2021
DOI: 10.1177/14653125211042891
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of living with a severe malocclusion: A review of the literature

Abstract: Aim: To facilitate the orthognathic shared decision-making process by identifying and applying existing research evidence to establish the potential consequences of living with a severe malocclusion. Methods: A comprehensive narrative literature review was conducted to explore the potential complications of severe malocclusion. A systematic electronic literature search of four databases combined with supplementary hand searching identified 1024 articles of interest. A total of 799 articles were included in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 113 publications
(183 reference statements)
0
5
1
1
Order By: Relevance
“…However, most of the participants in our study (85%) did not show elevated oxygen desaturation rates, despite the DFD diagnosis. The present data contrasts somewhat with the notion that severe malocclusion, as seen in DFD patients, is a risk factor for OSA [24]. Based on our preliminary results, it is possible to infer that anthropometric features, besides sex and age, might greatly in uence OSA detection in DFD patients.…”
Section: Discussioncontrasting
confidence: 99%
“…However, most of the participants in our study (85%) did not show elevated oxygen desaturation rates, despite the DFD diagnosis. The present data contrasts somewhat with the notion that severe malocclusion, as seen in DFD patients, is a risk factor for OSA [24]. Based on our preliminary results, it is possible to infer that anthropometric features, besides sex and age, might greatly in uence OSA detection in DFD patients.…”
Section: Discussioncontrasting
confidence: 99%
“…The associated pathological conditions of this injury include gingival surface injury, reduction of alveolar bone density and clinical attachment loss. 18 All these problems were identified in the cases group. The most severe grade of malocclusion in the present study resulted in the development of pyogranuloma.…”
Section: Discussionmentioning
confidence: 98%
“…Orthodontists are required to evaluate the dietary difficulties of their patients, however, this research identified no significant correlations between the dietary difficulties perceived by patients and those evaluated by their orthodontic postgraduates in both the physical and psychological aspects. Patients with severe malocclusion tend to have negative consequences of OHRQoL, as masticatory limitations may reduce the dietary intake performances [ 24 , 25 ]. However, there appear to be a number of external factors influencing the perceptions toward dietary difficulties apart from malocclusion and dental problems such as the time and location of a meal, and patients with different diet preferences may perceived their dietary difficulties differently [ 15 ].…”
Section: Discussionmentioning
confidence: 99%